ARCHITECTURE AS AN AESTHETIC FUNCTION OF HUMAN PRACTICAL ACTIVITY - Nadira Mamajonova; Abduganiyev Sardor; Toshpulatov Shokboston (Journals Park Publishing, 2022)
In this article, the first basic concepts about architecture, the main types, the basics of expression and design of uus are described in the process of preparing architects.
Keywords: tectura; arch; bas-relief